Krafla geothermal system, northeastern Iceland: Performance assessment of alternative plant configurations - LANGELLA, GIUSEPPE; PAOLETTI, VALERIA; Dipippoc, R.; AMORESANO, AMEDEO; Steinunnardóttir, K.; MILANO, MAURIZIO (Geothermics, 2017)
This paper deals with the Krafla geothermal field, northeastern Iceland, and illustrates how the upgrade of high enthalpy geothermal plants can be effective and lead to increased power production. The aim of this paper is to examine ways of improving the thermodynamic performance of the power plant at Krafla in light of the recent wells. Starting with an energetic and exergetic characterization of the geothermal site, the evolution over time and space was analyzed for the main geothermal parameters and the current energy potential. In light of several newly drilled wells with different characteristics from the previous wells, a number of alternative energy conversion systems are proposed for that installation, analyzing their performances with respect to the current system. The possibility of adding an extra pressure level to the current steam plant was analyzed along with the use of bottoming Organic Rankine Cycles (ORC). For the most promising alternatives, a thorough energy and exergy analysis was carried out including a thermodynamic optimization, in particular identifying a solution that would achieve a significant increase in both total electrical power producible and efficiency. The results are presented in tables and graphs and constitute a useful starting point for a potential reconfiguration.